Aspek Hukum Penguasaan Uang Milik Debitor Yang Dikuasai Kreditor Dalam Persfektif Prinsip Kepailitan - Cristi, Echa; Sunaryo, Sunaryo; S, Sepriyadi Adhan; Wiranata, I Gede AB; Kasmawati, Kasmawati (Universitas Sang Bumi Ruwa Jurai, 2025)
Bankruptcy law exists as a debt settlement mechanism for debtors who are no longer able to fulfill their obligations, with the main objective of creating certainty and justice in the distribution of bankruptcy assets to Creditors. However, in practice, problems often occur when money or assets belonging to the Debtor are physically controlled by one of the Creditors before or during the bankruptcy process. This research aims to analyze the legal aspects related to the control of the Debtor's money by Creditors in the bankruptcy process, by examining the principles of bankruptcy and legal protection for the parties. The method used is normative juridical legal research with a descriptive approach. The results of the study show that the actions of Creditors who hold money belonging to Debtors have the potential to violate the principle of equal treatment of creditors and the principle of general confiscation in bankruptcy law, and can interfere with the process of administering bankruptcy assets fairly and proportionally. Therefore, it is important that there is legal affirmation that protects the rights of debtors while upholding the principle of equal distribution for all creditors in the bankruptcy process